2017
DOI: 10.14196/mjiri.31.76
|View full text |Cite
|
Sign up to set email alerts
|

Organizational failure and turnaround in public sector organizations: A systematic review of the evidence

Abstract: Background: Existing evidence with regards to the organizational failure and turnaround are derived from the private sector. There is few corresponding review of the empirical evidence in the public sector. This review aimed at providing a summary of the research investigating the above items in the public sector. Methods: A search strategy was developed to identify empirical studies relating to organizational failure or turnaround process in public sector services on HMIC, Medline; SSCI, ASSIA, Business Sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Following the implementation of a turnaround strategy, a company can only be considered to have been turned around when its performance before and after the decline has changed faster than the industry average. Ravaghi, Mannion and Sajadi (2017) added that understanding the causes of decline and the factors that can lead to success is crucial if effective strategies are to be designed to counter underperformance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the implementation of a turnaround strategy, a company can only be considered to have been turned around when its performance before and after the decline has changed faster than the industry average. Ravaghi, Mannion and Sajadi (2017) added that understanding the causes of decline and the factors that can lead to success is crucial if effective strategies are to be designed to counter underperformance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This relationship has garnered unceasing attention from an array of stakeholders. For example, researchers, policymakers, and investors, considering the low productivity, poor performance and job turnover visible in public institutions (Ravaghi et al, 2017;Patanakul, 2014). To this effect, its observed that at Mbarara University of Science and Technology (MUST), job satisfaction has remained low exemplified by failure to meet their work targets, low levels of research output, offering less man hours per day and unwillingness to work beyond normal hours.…”
Section: Introductionmentioning
confidence: 99%